Guliyev, Ramiz - (:unkn) unknown (My University, 2026)
Ramiz Mirmahmud oglu Guliyev graduated with honors from the Voronezh Agricultural Institute in 1980, specializing in Land Management. In the same year, he was appointed by the Ministry of Agriculture of the former USSR to the Azerbaijan Agricultural Institute to pursue scientific and academic activities. From 1981 to 1984, he completed full-time postgraduate studies at the Voronezh Agricultural Institute and in 1984 successfully defended his Candidate of Sciences dissertation at the Moscow Institute of Land Management Engineers. He subsequently continued his academic career at the Azerbaijan Agricultural Academy, where he served as Head of the Department of Land Management and later as Vice-Rector for Academic Affairs and Acting Rector. In 2006, Professor Guliyev was awarded the degree of Doctor of Agricultural Sciences, and in 2011 he attained the academic rank of Professor. From 2009 to 2020, he held senior positions in the Real Estate Cadastre and Address Registry system under the State Committee on Property Issues. During this period, under his leadership, Azerbaijan’s first electronic cadastral registration of the unified land fund was implemented, an electronic cadastral information system was established, and digital cadastral maps were developed. He also played a leading role in the implementation of addressing reforms and the establishment of the Address Registry Information System. Since 2023, Professor Guliyev has been working as a Professor at the Department of Geomatics at the Azerbaijan University of Architecture and Construction. He is the author of more than 115 scientific articles, 6 textbooks, 3 study manuals, 2 monographs, and numerous course programmes and methodological guidelines. His research interests include land management, real estate cadastre, geospatial information systems, digital cadastral mapping, and address registry systems.